Aestheticizing Coexistence: Public Perceptions of the Istiqlal-Cathedral Tunnel on Social Media - Muhammad Yusuf Pratama; Luthfi Rahman; Mokh Sya'roni; Yasser Mulla Shadra; Muhammad Alwi HS (KARSA Journal of Social and Islamic Culture, 2025)
Although Indonesia is known for its religious diversity, numerous incidents of intolerance reveal that symbols and practices of tolerance have yet to be deeply rooted in the country's social fabric. the Terowongan Silaturahmi in this context, a connecting passage between the Istiqlal Mosque and the Jakarta Cathedral—stands out as a rare spatial phenomenon symbolizing interfaith harmony in an urban landscape. This study aims to examine the aesthetic and architectural dimensions of the tunnel and analyze public perceptions of it as a representation of pluralist values. Employing a qualitative-descriptive approach supported by digital quantitative analysis, the study integrates architectural interpretation, literature review, and sentiment classification of 2,003 comments from 5 videos on the YouTube page using the IndoBERT model and word cloud visualization. The findings reveal that the tunnel is broadly perceived as a positive symbol of tolerance and national identity, though some resistance emerges from conservative groups. Therefore, the Terowongan Silaturahmi exempli-fies how architecture can function as a medium for dialogue and social education on interfaith coexistence within Indonesia's public spaces.